Left ventricular hypertrophy after hypertensive pregnancy disorders. Issue 19 (4th August 2015) - Scantlebury, Dawn C; Kane, Garvan C; Wiste, Heather J; Bailey, Kent R; Turner, Stephen T; Arnett, Donna K; Devereux, Richard B; Mosley, Thomas H; Hunt, Steven C; Weder, Alan B; Rodriguez, Beatriz; Boerwinkle, Eric; et al.
Abstract : Objective: Cardiac changes of hypertensive pregnancy include left ventricular hypertrophy (LVH) and diastolic dysfunction. These are thought to regress postpartum. We hypothesised that women with a history of hypertensive pregnancy would have altered LV geometry and function when compared with women with only normotensive pregnancies. Methods: In this cohort study, we analysed echocardiograms of 2637 women who participated in the Family Blood Pressure Program. We compared LV mass and function in women with hypertensive pregnancies with those with normotensive pregnancies. Results: Women were evaluated at a mean age of 56 years: 427 (16%) had at least one hypertensive pregnancy; 2210 (84%) had normotensive pregnancies. Compared with women with normotensive pregnancies, women with hypertensive pregnancy had a greater risk of LVH (OR: 1.42; 95% CI 1.01 to 1.99, p=0.05), after adjusting for age, race, research network of the Family Blood Pressure Program, education, parity, BMI, hypertension and diabetes. When duration of hypertension was taken into account, this relationship was no longer significant (OR: 1.19; CI 0.08 to 1.78, p=0.38). Women with hypertensive pregnancies also had greater left atrial size and lower mitral E/A ratio after adjusting for demographic variables. The prevalence of systolic dysfunction was similar between the groups. Conclusions: A history of hypertensive pregnancy is associated with LVH after adjusting for risk factors; this might be explained by longer duration of hypertension. This finding supports current guidelines recommending surveillance of women following a hypertensive pregnancy, and sets the stage for longitudinal echocardiographic studies to further elucidate progression of LV geometry and function after pregnancy. Clinical trial registrations: GENOA- NCT00005269 ; HyperGEN- NCT00005267 ; Sapphire- NCT00005270 ; GenNet- NCT00005268 .